Preparing a patient with a stoma for self-care taking into consideration dermatological and surgical complications - Kózka, Maria; Bazaliński, Dariusz; Cipora, Elżbieta (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2010)
Introduction: In Poland, every year about 400 surgical creations of a stoma from the small intestine (ileostomy) and 2000 colonostomies (from the colon) are performed. Preparing patients for self-reliance and self-care as well as full social integration are important elements of care of patients with the stoma. It is possible to achieve the intended purpose through providing the patient with individualised care according to the model recommended by the Polish Proctology Club. In this model the authors emphasize factors, which determine the onset of patient\'s self-care. These factors include: choosing the site for stoma, stoma complications, patient\'s knowledge and skills related to stoma care and patient\'s individual possibilities. Aim of the study: The objective of this study was to evaluate patient\'s readiness for self-care taking into consideration possible dermatological and surgical complications among individuals with the stoma. Material and methods: The study included 160 patients with the stoma for at least two months. A survey questionnaire using a tool developed by the authors was applied. Relations between variables were examined with Pearson\'s correlation coefficient and the chi-square test with the level of confidence p below 0.05. Results and conclusions: The study showed that 55% of respondents didn’t have any site of stoma marked before the surgery and the range of information regarding stoma care was insufficient. There was no information about the following aspects: stoma irrigation procedure – confirmed by 74.4% of respondents, exercises improving abdominal muscles – 59.4%, and 53.7% of participants didn’t receive any information about possible stoma complications. Surgical complications were recorded in 48% of respondents including peristomal hernia (28%), stoma prolapse (15%), and wrong localisation of the stoma (5%). Dermatological complications were observed in 56.6% of patients.